Regulating Hawala : informal remittances post 9/11 - Beswick, Claire; Ahwireng-Obeng, Fred ([London] : SAGE, 2016)
In 2010, the officials of the Financial Action Task Force (FATF) were reviewing the problems of formalising informal financial systems in developing countries, and specifically addressing the hawala system in Africa. Hawala was a highly popular form of remittance transfer, especially where there were no banks or the banking system failed to offer clients ease of access and competitive costs. However, hawala was open to misuse as a means for both money laundering and the funding of terrorism. They wondered if and how the FATF could address these problems and whether its existing recommendations and interventions were sufficient.
Originally Published in: Beswick, C., & Ahwireng-Obeng, F. (2013). Regulating Hawala: Informal Remittances Post 9/11. WBS-2013-18. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Hawala system -- Case studies; Financial services industry -- Standards -- Case studies